2018
DOI: 10.2147/cia.s154234
|View full text |Cite
|
Sign up to set email alerts
|

Functionality and Outcome in Older Patients with Severe Aortic Stenosis (FOOPAS): an interdisciplinary study concept for a prospective trial

Abstract: BackgroundFrailty is a geriatric syndrome that can influence mortality and functional recovery after treatment of severe aortic stenosis (AS). The integration of standardized geriatric assessment (GA) in clinical practice is limited by a lack of consensus on how to measure it.ObjectivesThis study aims to compare the incremental predictive value of different frailty scales to predict the outcomes following surgical aortic valve replacement, transcatheter aortic valve implantation, and conservative treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Our data confirm that the Katz frailty syndrome is a significant indicator of mortality in patients after TAVI and these data are consistent with the results presented in previous publications and meta-analysis [11,[13][14][15][16][18][19][20]. At the same time, we showed that 1-year all-causes mortality after TAVI in high-risk and intermediate-risk patients was a significantly dependent on Katz frailty score.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data confirm that the Katz frailty syndrome is a significant indicator of mortality in patients after TAVI and these data are consistent with the results presented in previous publications and meta-analysis [11,[13][14][15][16][18][19][20]. At the same time, we showed that 1-year all-causes mortality after TAVI in high-risk and intermediate-risk patients was a significantly dependent on Katz frailty score.…”
Section: Discussionsupporting
confidence: 93%
“…However, they do not include factors such as cognitive decline and difficulties in independent daily activity, and have limitations in predicting mortality in the population of patients undergoing transcatheter aortic valve implantation (TAVI). Several studies have shown that frailty is associated with higher morbidity and all-causes mortality in patients undergoing cardiac surgery or TAVI [13][14][15][16][17]. In our group, the frailty syndrome concerned all patients, and 48% in the advanced stage.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Guidelines for clinical management in cardiology emphasize the need to monitor FS and search for its reversible causes in the elderly (Ponikowski et al, 2016). Despite the widespread importance of FS in clinical management, there are no explicit cardiological guidelines adopting a specific definition of FS and requirements for applying methods of its identification (Vogt et al, 2018). In cardiology, there are no standardized methods in clinical decisions-making based on FS, as it is still being diagnosed with the patient's foot-of-the-bed assessment or the so-called "eyeball test" (Bridgman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2 With regard to mortality, SAVR and TAVI result in good outcomes among older patients. 3 In contrast, some patients with AS are inoperable because of their clinical status or comorbidities, 1 and up to 40% of patients with severe AS still do not undergo SAVR or TAVI. 4 These patients may experience stroke, bone fractures resulting from falls, and disuse syndrome.…”
mentioning
confidence: 99%